EVALUATION OF AESTHETICS IN DANCE WITH SPECIAL REFERENCE TO KATHAK - Dr Indira Bali (IJRDO- Journal of Educational Research, 2016)
Dance in India has always been a profound expression of human emotions and spiritual experiences. The classical dance form of Kathak, rooted in ancient storytelling traditions, offers a unique perspective on aesthetic appreciation. The aim of this paper is to evaluate the aesthetic principles inherent in Kathak, drawing from both ancient Indian treatises and contemporary dance theory. The author has proposed a seven point evaluation scale for evaluation of aesthetics in dance, which can be applied by dance teachers, scholars, researchers or any individual who wishes to identify the best inherent qualities of a dance performance or a dancer in a competitive set up or as a feedback after training sessions. This research paper is an extract from the unpublished PhD research work of the author which is an original research work. *(The author is an Assistant Professor in the Department of Dance, Faculty of Arts & Culture, at Punjabi University,Patiala.)